Student motivation to study music and sport – a comparison between study subjects and study programs on intrinsic and extrinsic motivational aspects - Immerz, Anna; Nusseck, Manfred; Hohagen, Jesper; Spahn, Claudia (Frontiers in Psychology, 2024)
In both subjects, music and sport, the engagement with the subject contentlearning an instrument or training in a sports clubusually begins in early childhood. This makes these subjects special and similar. It is therefore of interest to examine the motivation for choosing music and sport as subjects for university study.In the present investigation, 151 students at the beginning of their university studies were examined. Among these were 110 music university students in the Bachelor of Music (B.Mus.) and music teacher education program, and 41 sport university students in the Bachelor of Science (B.Sc.) and sport teacher education program. The study contained a custom-made questionnaire on sociodemographic data, questions on study choice alternatives and biographical musical or sporting background, as well as two standardized questionnaires on motivation for enrollment (STUWA) and on aspects that are important for the profession.Music and sport students were at a rather high and similar level of intrinsic motivation to study their subjects. However, materialistic goals motivated the teacher education students more than the bachelor's students with an artistic program. The difference between the study programs was also found in the context of extrinsic-social motivation, where the teacher training students answered with higher scores. With regard to socially-induced motivation, it was shown that music students and sport teacher education students were more socially induced to study the respective subject compared to the general student population. With regard to uncertainty when choosing a course, it was found that Bachelor of Music students were more certain that they wanted to study exactly their particular subject. The ages at which music and sport were started in childhood were similar, but the first-year music students were younger than the sport students were. Compared to sports students, music students decided their area of study earlier, and bachelor's students in music in particular had fewer alternative study options than sports students. The results provide a differentiated picture of student motivation to study and thus allow a deeper insight into the subject cultures of music and sport. They also open up opportunities for follow-up studies in comparison with other study subjects and programs.